Conceptual Metaphor in Kahitna’s Song Lyrics - Jannah, Raudlotul; Istiqomah, Khusnul (NOBEL: Journal of Literature and Language Teaching, 2021)
Every song has lyrics and every lyric undeniably contains one or two messages or ideas that a songwriter wants to express. That being said, songwriters usually use conceptual metaphors to make their songs aesthetically audible and emotionally evoking to the heart of the listeners when they hear the song or when they understand of what was written in the lyrics. Unlike the previous research that merely focused on the types of conceptual metaphors but failed to analyze the image schemas of the metaphors, this research aims at finding and describing how conceptual metaphors as well as the image schemas of the metaphors are used in Kahitna’s song lyrics. The data were analysed on the basis of Conceptual Metaphor Theory from Lakoff and Johnson’s (1980) and Kovecses’s (2010) and also Saeed’s Image Schema (2016). The research shows that there are nine conceptual metaphors found in Kahitna’s song lyrics: “Passion of Love is Sea,” “Love Story is Journey,” “Difficulty in Relationship is Journey,” “Goal of the Lovers is Journey,” “Deepest Heart is Sea,” “Heart is Container,” “Love is Container,” “Love is Concrete Object,” and “Longing is Waves.” In addition, Containment schema, Path Schema, and Force Schema are also found in this research.